2011
DOI: 10.1016/j.bpj.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cytoplasmic Gag-Gag Interactions by Dual-Color Z-Scan Fluorescence Fluctuation Spectroscopy

Abstract: Fluorescence fluctuation spectroscopy (FFS) quantifies the interactions of fluorescently-labeled proteins inside living cells by brightness analysis. However, the study of cytoplasmic proteins that interact with the plasma membrane is challenging with FFS. If the cytoplasmic section is thinner than the axial size of the observation volume, cytoplasmic and membrane-bound proteins are coexcited, which leads to brightness artifacts. This brightness bias, if not recognized, leads to erroneous interpretation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 29 publications
6
47
0
Order By: Relevance
“…Based on in vivo cross-linking, Kutluay and Bieniasz (89) concluded that the most abundant HIV-1 species in the cytoplasm is monomeric. Fogarty et al (90) came to a similar conclusion using multiphoton microscopy coupled with quantitative fluorescence fluctuation analysis of Gag-GFP (91,92). With this technology, it is possible to estimate the actual molar concentration of Gag-GFP in the cytoplasm.…”
Section: Amentioning
confidence: 84%
“…Based on in vivo cross-linking, Kutluay and Bieniasz (89) concluded that the most abundant HIV-1 species in the cytoplasm is monomeric. Fogarty et al (90) came to a similar conclusion using multiphoton microscopy coupled with quantitative fluorescence fluctuation analysis of Gag-GFP (91,92). With this technology, it is possible to estimate the actual molar concentration of Gag-GFP in the cytoplasm.…”
Section: Amentioning
confidence: 84%
“…The fluorescently labeled Gag excited during the scan gives rise to a z-scan intensity profile (Fig. 2B and D), which provides information about the axial distribution of the Gag-eYFP at the scan location (61). Fitting of the z-scan intensity profile separates the fluorescence contributions from the cytoplasmic and the PM-bound protein populations (35,36).…”
Section: Methodsmentioning
confidence: 99%
“…First, the intensity profile of the red channel (mCherry) was corrected for spectral cross talk from the eYFP signal and fit to determine the location and thickness of the cytoplasmic volume occupied by mCherry (61). Second, the intensity trace of eYFP was fit to a model that allows Gag-eYFP to be located at the ventral and dorsal PM and in the cytoplasm with the cytoplasmic location and thickness determined by the fit of the mCherry z-scan intensity profile.…”
Section: Methodsmentioning
confidence: 99%
“…Finally we applied our technique to study the membrane interactions of the matrix domain of human T-cell leukemia virus type 1 (HTLV-1) Gag. We previously observed that the Gag polyprotein and matrix (MA), its membrane-binding domain, of HTLV-1 interact with the plasma membrane at low cytoplasmic concentrations, which is in stark contrast with the corresponding proteins of the human immunodeficiency virus type 1 (HIV-1) (11)(12)(13). Here we expand our investigation of HTLV-1 virus assembly by characterizing the membrane binding curve for the MA domain of HTLV-1 Gag and the lipid-specificity of the interaction.…”
Section: Introductionmentioning
confidence: 99%